Development of Worksheets Based on the Metaphorical Thinking Approach for Students’ Procedural Fluency Ability - Sartika, Nenden Suciyati; Kusuma, Yaya S.; Martadiputra, Bambang Apiv Priatna; Ditasona, Candra; Safitri, Mia Millawaty (Brillo Journal, 2022)
The mathematics materials in learning mostly used package books, but the provided resources in the school were limited and teachers did not optimize the existing technology to provide effective and interesting materials. As a consequence, students did not complete the exercise according to mathematical procedures and they were pessimistic. The general research purpose was to produce a metaphorical thinking approach-based worksheet for students' procedural fluency on valid characteristics. This study used research and development by the ADDIE stage model. The participant was 9th-grade students in junior high school. Data collection were observation, questionnaires, and interview techniques. The results showed that the characteristics of the developed worksheet have been valid. The results of the worksheet validity test were obtained by 90% and the results of the trial of students were 93%. The implications of this worksheet are helpful for students to independent learning, and this worksheet helps students solve mathematical problems in accordance with procedural, assisted by steps of the metaphorical thinking approach, teaching and learning activities are more effective.